1995
DOI: 10.1074/jbc.270.35.20309
|View full text |Cite
|
Sign up to set email alerts
|

The CryIA(c) Receptor Purified from Manduca sexta Displays Multiple Specificities

Abstract: The kinetic binding characteristics of four Bacillus thuringiensis CryI insecticidal crystal proteins to a Cry-binding protein, purified from Manduca sexta brush-border vesicles, were analyzed by an optical biosensor. This 120-kilodalton binding protein, previously determined to be aminopeptidase N, was converted to a 115-kilodalton water-soluble form by removing the attached glycosylphosphatidylinositol anchor with phospholipase C. The solubilized form recognized the three major subclasses of CryIA toxins but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
163
2
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(179 citation statements)
references
References 45 publications
13
163
2
1
Order By: Relevance
“…GalNAc efficiently competes the binding of Cry1Ac to APN by binding to a pocket located in domain III (25,44,45). This suggests the Cry1Ac epitope that binds scFv73 is different than that known for initially binding to APN, and as our results suggest, is located on domain II.…”
Section: Competition Of Cry1ab Toxin Binding To M Sexta Bbmv Withmentioning
confidence: 99%
See 1 more Smart Citation
“…GalNAc efficiently competes the binding of Cry1Ac to APN by binding to a pocket located in domain III (25,44,45). This suggests the Cry1Ac epitope that binds scFv73 is different than that known for initially binding to APN, and as our results suggest, is located on domain II.…”
Section: Competition Of Cry1ab Toxin Binding To M Sexta Bbmv Withmentioning
confidence: 99%
“…The interaction between toxin and its receptor can be complex. For example, Cry1Ac binds to two sites on the APN purified from M. sexta, and only one of these sites is also recognized by Cry1Aa and Cry1Ab (25). Interestingly, binding of Cry1Ac to both receptor sites is inhibited by sugars, which do not inhibit the binding of Cry1Aa and Cry1Ab (25).…”
mentioning
confidence: 99%
“…The affinity constant (K d ) obtained by SPR analysis of the Cry1Ac interaction with APN isolated from M. sexta was two orders of magnitude lower than that reported from equilibrium binding studies with Cry1Ac and intact M. sexta BBMV [4,19]. The SPR experiments used APN covalently attached to a carboxymethylated dextran matrix, in the absence of other membrane components.…”
Section: Introductionmentioning
confidence: 99%
“…The SPR experiments used APN covalently attached to a carboxymethylated dextran matrix, in the absence of other membrane components. It was suggested that the presence of other molecules in BBMV, particularly lipid, might be responsible for the observed differences [19]. The fact that Cry toxin binding to BBMV from susceptible insects is quickly irreversible [22], indicating toxin insertion into the membrane, could account for the higher affinity of Cry1Ac for intact BBMV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation